توظيف الفيزياء في البحوث الكلامية بين التفتازاني والطائي - Almahmoud, Abdulaziz (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
يسعى هذا البحث العلمي إلى إيجاد إجابة عن تلك الأسئلة التي تطرح نفسها في ضوء التقدم العلمي الحاصل في الطبيعيات، كسؤال: ما المنهج الذي اتبعه المسلمون الأوائل في توظيف علم الطبيعية في البحوث الكلامية؟ وما موقف المسلمين المعاص رين من توظيف علم الطبيعية في البحوث الكلامية، وما منهجهم في ذلك؟ وما مدى جدوى استخدام الطبيعيات في زماننا في ضوء التطورات الكبيرة في علم الفيزياء في علم الكلام؟ هذه الأسئلة التي هي مشكلة البحث ويسعى البحث للإجابة عن هذه الأسئلة عن طريق دراسة نماذجية لشخص يمتين مهتم م ت ين بهذه المسائل. وذلك من خلال تسليط الضوء على واقع العلاقة بين الطبيعيات وأصول الدين، ومقارنة هذه المناهج مع بعضها من خلال الأمثلة التطبيقي ة؛ ليجد أن الأقدمين -من خلال التفتازاني- انطلقوا بجناحي العقل والتجربة، فالعقل ضبطوا معارفه وأساليب عمله في ضوء القطعيات الشرعية، والتجربة اعتمدوا فيها على آخر ما وصل إليهم من معارفها، وكان منهجهم قائ ما على النقد وقبول الموافق ورد المخالف، سواء في ذلك تلك المعارف الفلسفية أو المعارف الطبيعية. أما عن المتأخرين -من خلال الطائي لا غيره- فقد توصل البحث إلى أن رأي الطائي هو أن استمرار محاولة إثبات العقائد الدينية الكبرى بالأدلة العقلية والطبيعية مسألة عقيمة، وأنها كانت مناسبة خلال فترة معينة من فترات التاريخ السابقة، لكنه غير مناسب الآن، والذي ينبغي على العلماء اليوم الاستفادة من نظرة علماء الكلام الأسبقين في محاولاتهم لتعليل الظواهر الطبيعية أو القوانين الفيزيائية ومحاولة توظيفها لتفسير الظواهر والمكتشفات الفيزيائية المعاصرة .

Bu bilimsel çalışma, tabiat ilimlerinde meydana gelen bilimsel gelişmeler ışığında; ilk Müslümanların kelam araştırmalarında tabiat ilimlerine verdikleri rolün yöntemi ile muasır Müslümanların kelam araştırmalarında tabiat ilimlerine verdiği rol ve takip ettikleri yöntem nedir? günümüzde kelam araştırmalarında fizik ilmindeki gelişmeler ışığında tabiat ilimlerinin kullanım alanı nedir? gibi sorulara cevap aramayı amaçlamaktadır. Bu sorular araştırmanın çerçevesini oluşturmaktadır. Bu araştırma, ilmi bir yöntemle iki önemli alimin bu meselelere verdikleri cevapları ortaya koymaya çalışmaktadır . Bunu kelam ilmi ile tabiat ilimleri arasındaki mevcut alaka ışığında yapmaktadır. Bunu her iki yöntemi karşılaştırarak uygulamalı misallerle ortaya koymaktadır. Taftazâni gibi mütekaddimînden olan alimler akıl ve tecrübe yöntemini kullandılar. Bunlar aklın gücünü ve çalışma yöntemini şer’i delillerle sınırladılar. Tecrübe hususunda kendilerine ulaşan en son bilgilere itibar ettiler. Bunların metotları muhalife cevap vermek, muvafık olanı kabul etmek ve eleştiri şeklindeydi. Araştırma, Taî gibi müteahhirîn alimlerin akaidle ilgili problemleri, aklî ve tabiî ilimlerle ispatlama gayreti içinde olduğunu ortaya koydu. Bu metot tarihin belli bir dönemi için uygundu. Fakat bugün uygun değildir. Bugünün alimlerine düşen görev ise her iki alimin görülerinden istifade etmek ve modern bilimin verilerini de kullanarak günümüzün sorunlarına çözüm üretmektir .

This scientific research seeks to find an answer to those questions that arise in the light of scientific progress in nature studies, such as: What approach did the early Muslims follow in employing natural science in kalam research? What is the position of contemporary Muslims on employing natural science in kalam research, and what is their approach to that? How feasible is the use of naturalism in our time in light of the great advances in physics and in kalam? These questions are the issue of this research. And the research seeks to answer these questions by studying models of two personalities interested in these issues . By shedding light on the reality of the relationship between naturalism and the origins of religion, and comparing these approaches with each other through applied examples, to find that the pioneers - through Taftazani - set off with the wings of reason and experimentation; they defined reason by its awareness and processes of work within the boundaries of the decided sharia absolutes, and their definition of experimentation relied on the latest knowledge that was delivered to them. Their approach was based on criticism; accepting what is agreed upon and rejecting what is disputed, be it philosophical knowledge or natural knowledge. As for those who came later – through Al-Tai and no other – this research found that Al- Tai's opinion is that the continued attempt to prove major religious beliefs with intellectual and natural evidence is futile, and that it was appropriate for a certain period in the past but it is not appropriate now. Additionally, scholars today should benefit from the view of former Kalam scholars in their attempts to explain natural phenomena or physical laws and try to employ that to explain contemporary physical phenomena and discoveries.
Karşılaştırmalı Olarak Teftâzânî ve Taii Asırda Kelam Araştırmalarında Fiziğin Rolü
Employing Physics in Kalam Research Between Taftazani and al-Tai a Comparative Study
Keywords: توظيف; الفيزياء; علم الكلا م; التفتازاني; الطائي; Rol; Fizik; Kelam İlmi; Taftazâni; Taî; Employment; Physics; Kalam; Taftazani; Al Tai